2017
DOI: 10.1038/s41598-017-03201-1
|View full text |Cite
|
Sign up to set email alerts
|

How impaired efficacy happened between Gancao and Yuanhua: Compounds, targets and pathways

Abstract: As recorded in Traditional Chinese Medicine (TCM) theory, Gancao (Glycyrrhizae Radix et Rhizoma) could weaken the pharmacological effect or increase the toxicity of Yuanhua (Genkwa Flos). However, the theory has been suspected due to lack of evidence. Here, we investigate whether Gancao could weaken Yuanhua’s diuretic effect, if so, which chemicals and which targets may be involved. Results showed that Yuanhua exerted diuretic effect through down-regulating renal AQP 2, without electrolyte disturbances such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Prior chemical studies have shown that Genkwa flos encompasses various types of constituents involving flavonoids, diterpenoids, lignans, and coumarins [ 100 ]. Current emerging evidence indicates that severe lesions to cardiac, renal, hepatic, and cutaneous tissues can be identified by excessive and prolonged administration of Genkwa flos [ 101 , 102 , 103 , 104 ]. Hepatotoxicity of Genkwa flos treatment have shown in HL-7702 liver cells, such as the increased hepatic serum makers of ALT, AST, and MDA, and downregulated oxidative stress indexes of CAT and GSH.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…Prior chemical studies have shown that Genkwa flos encompasses various types of constituents involving flavonoids, diterpenoids, lignans, and coumarins [ 100 ]. Current emerging evidence indicates that severe lesions to cardiac, renal, hepatic, and cutaneous tissues can be identified by excessive and prolonged administration of Genkwa flos [ 101 , 102 , 103 , 104 ]. Hepatotoxicity of Genkwa flos treatment have shown in HL-7702 liver cells, such as the increased hepatic serum makers of ALT, AST, and MDA, and downregulated oxidative stress indexes of CAT and GSH.…”
Section: Molecular Mechanisms Involved In Tcm-induced Oxidative Hementioning
confidence: 99%
“…System pharmacology is emerging as a holistic and efficient tool to study the role of TCM due to its capable of describing complex interactions between drugs and biological systems including the human body, organs, and diseases from a network perspective (Kloft et al, 2016 ; Zhang et al, 2016 ). Combined with pharmacology and pharmacodynamics, it has been successfully applied to interpret the synergistic mechanisms of herb combinations at molecular network level (Zhou et al, 2016 ; Yu et al, 2017 ; Yue et al, 2017 ). In the present study, we tried to establish the compound-target (C-T), target-pathway (T-P), and target-organ (T-O) networks by the system pharmacology model based on chemical, pharmacokinetic and pharmacological data at the system, organ, and molecular levels (Supplementary Figure S2 ), so as to uncover the underlying synergistic mechanisms of Huangqi and Huanglian for treating DM.…”
Section: Introductionmentioning
confidence: 99%
“…The urinary excretion volume was mainly determined by the urine concentrating ability, including urine and its electrolyte reabsorption [13, 16]. In this study, we explored the diuretic activity of LS and its four fractions (LSA, LSB, LSC, and LSD) compared with that produced by furosemide in normal rats.…”
Section: Discussionmentioning
confidence: 99%